2013
DOI: 10.1152/ajprenal.00230.2013
|View full text |Cite
|
Sign up to set email alerts
|

Novel diuretic targets

Abstract: As the molecular revolution continues to inform a deeper understanding of disease mechanisms and pathways, there exist unprecedented opportunities for translating discoveries at the bench into novel therapies for improving human health. Despite the availability of several different classes of antihypertensive medications, only about half of the 67 million Americans with hypertension manage their blood pressure appropriately. A broader selection of structurally diverse antihypertensive drugs acting through diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 161 publications
0
28
0
Order By: Relevance
“…Recent advances in the small-molecule pharmacology by our group [39,40] and Merck [41] are providing critically needed tools for exploring Kir1.1 as a therapeutic target for hypertension. This work has been reviewed recently by our group [42] as well as by Garcia and Kaczorowski (2013) in this issue of Current Opinion in Pharmacology and will not be discussed further.…”
Section: Cardiac Kir2x Channelsmentioning
confidence: 99%
“…Recent advances in the small-molecule pharmacology by our group [39,40] and Merck [41] are providing critically needed tools for exploring Kir1.1 as a therapeutic target for hypertension. This work has been reviewed recently by our group [42] as well as by Garcia and Kaczorowski (2013) in this issue of Current Opinion in Pharmacology and will not be discussed further.…”
Section: Cardiac Kir2x Channelsmentioning
confidence: 99%
“…Type-B intercalated cells represent the only site where chloride can be actively reabsorbed (entry through apical Cl - /HCO 3 - exchange via pendrin, and exit from basolateral chloride channels) [5]. Due to these features, pendrin has been proposed as a novel diuretic target [16,17,18]. In support of this possibility, a recent study showed that double deletion of the Na + /Cl - cotransporter (NCC) and pendrin leads to sodium wasting, hypovolemia, and hypotension [19].…”
Section: Introductionmentioning
confidence: 99%
“…Increased fluid delivery specifically stimulates K ϩ secretion through flow-sensitive largeconductance Ca 2ϩ -activated K ϩ (BK) channels. Thus loop or thiazide diuretic use leads to urinary K ϩ excretion and hypokalemia (2).…”
mentioning
confidence: 99%